Magnetic Resonance Imaging of Adipose Tissue in Metabolic Dysfunction - Franz, Daniela; Syväri, Jan; Weidlich, Dominik; Baum, Thomas; Rummeny, Ernst J; Karampinos, Dimitrios C. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Background Adipose tissue has become an increasingly important tissue target in medicine. It plays a central role in the storage and release of energy throughout the human body and has recently gained interest for its endocrinologic function. Magnetic resonance imaging (MRI) is an established method for quantitative direct evaluation of adipose tissue distribution, and is used increasingly as the modality of choice for metabolic phenotyping. The purpose of this review was the identification and presentation of the currently available literature on MRI of adipose tissue in metabolic dysfunction.Method A PubMed (http://www.ncbi.nlm.nih.gov/pubmed) keyword search up to August 2017 without starting date limitation was performed and reference lists of relevant articles were searched.Results and Conclusion MRI provides excellent tools for the evaluation of adipose tissue distribution and further characterization of the tissue. Standard as well as newly developed MRI techniques allow a risk stratification for the development of metabolic dysfunction and enable monitoring without the use of ionizing radiation or contrast material.Key points Citation Format
Keywords: MR imaging; MR spectroscopy; adipose tissue; brown fat; metabolic disorders